Over a million students use our free study notes to help them with their homework
= 14x+21y-14x+xy
=y(21+x)
- We can write sqrt(12) as sqrt (4*3).
- This can be written as sqrt(4) * sqrt(3)
- We know the squ...
First, multiply all terms by (x - 1) to remove the quotient, and multiply out of the brackets: 3x + 2 + 3(x - 1) = 4(x - 1) >>> 3x + 2 + 3x - 3 = 4x - 4. Next, group all like terms on either side...
First of all, when we expand brackets we know that the x will be at the start of the brackets
(x )(x )= 0
Look a the equation again, x2+5x+6=0. All of our numbers are posit...
Some students struggle to solve equations with unknowns on both sides. I think the easiest way to solve these types of equations is to use the balance method. This is where you treat the equation like a w...
←
588
589
590
591
592
→
Internet Safety
Payment Security
Cyber
Essentials